2012
DOI: 10.18584/iipj.2012.3.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging in the Urban School Environments of Aboriginal Youth

Abstract: It is well established that educational attainment and social support are critical social determinants of health among Aboriginal Canadians. Still, the gap in educational attainment with non-Aboriginal Canadians continues to grow, and little is known about the role of social support as a health determinant among Aboriginal youth. In collaboration with The Wabano Centre for Aboriginal Health (Ottawa, Canada), we undertook focus groups with urban Aboriginal youth at-risk to examine perceptions of their urban sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…To reflect the risk to health and wellbeing risk from flooding, we used a holistic view of health, based on the Māori indigenous model of health, ‘Te whare tapa whā’ (the house of four walls), which holds that hauora (wellbeing) is made of the four aspects of physical, mental, spiritual and social wellbeing [ 57 ]. This is similar to whole-life views of health of indigenous peoples in other countries, such as Australia [ 58 ] and Canada [ 59 ], as well as the World Health Organization’s definition of health as ‘a complete state of physical, mental and social wellbeing, and not merely the absence of disease or infirmity’ [ 60 ].…”
Section: Resultssupporting
confidence: 68%
“…To reflect the risk to health and wellbeing risk from flooding, we used a holistic view of health, based on the Māori indigenous model of health, ‘Te whare tapa whā’ (the house of four walls), which holds that hauora (wellbeing) is made of the four aspects of physical, mental, spiritual and social wellbeing [ 57 ]. This is similar to whole-life views of health of indigenous peoples in other countries, such as Australia [ 58 ] and Canada [ 59 ], as well as the World Health Organization’s definition of health as ‘a complete state of physical, mental and social wellbeing, and not merely the absence of disease or infirmity’ [ 60 ].…”
Section: Resultssupporting
confidence: 68%
“…Jing- Lu (2015) found that a sense of belonging influences organizational commitment, work motivation, job satisfaction, and work performance. Richmond & Smith (2012) also found that experiencing a sense of belonging will help in achieving an educational goal. This educational goal in an organization's learning can foster employees' motivation and performances.…”
Section: Literature Review Sense Of Belongingmentioning
confidence: 95%
“…From this information, it may be speculated that although focus group locations were often held in convenient locations (as per focus groups) instead of ceremonial locations (as per sharing circles), conducting interviews within the Indigenous communities provided a level of cultural relevance that aided the blending of these two methods. Interestingly, of the six studies that took place in urban settings (Brown et al, 2016;Kelley et al, 2019;Kulis et al, 2011;Restoule, 2011;Richmond & Smith, 2012;Smillie-Adjarkwa et al, 2013), one of these studies was conducted at a location that offered services and programming for Indigenous youth (Richmond & Smith, 2012), providing further cultural relevance. Facilitation.…”
Section: Blending Of Sharing Circle and Focus Group Methodsmentioning
confidence: 99%